First, let's find g(4). After we find it, we can substitute the value into
.
To find g(4), we need to substitute x = 4 into the function
, as shown below:
![g(x) = x^2 - 7](https://img.qammunity.org/2019/formulas/mathematics/high-school/2ike889z9cwwz7u8lwyl7kx29llqm2as18.png)
![g(4) = 4^2 - 7](https://img.qammunity.org/2019/formulas/mathematics/high-school/zl33b6qfatp82cl1pcfte9kqiifqkw287i.png)
![g(4) = 9](https://img.qammunity.org/2019/formulas/mathematics/high-school/opci8nh0lsjlx4pcncjb8vyf52uh6jj5xh.png)
Now that we have found g(4) = 9, we can substitute this value in for
in
.
![f(x) = 3x + 1](https://img.qammunity.org/2019/formulas/mathematics/middle-school/kxsjsxgalbr1fht8cf3ve7x3wddey8bke3.png)
![f(9) = 3(9) + 1](https://img.qammunity.org/2019/formulas/mathematics/high-school/tbpn9vegga5ea46lu6phtrmcoryyhslshn.png)
![f(9) = 28](https://img.qammunity.org/2019/formulas/mathematics/high-school/9akiry00m6l7eln6iindw2w1ox7zfl3g56.png)
f(g(4)) is equal to 28.